2004
DOI: 10.1097/01.fjc.0000166291.72324.eb
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Shift of Endothelin Receptor Subtypes in Dogs with Heart Failure Produced by Rapid Ventricular Pacing

Abstract: To clarify the functional role of endothelin-A/endothelin- B (ETA/ETB) receptors in congestive heart failure (CHF), we examined the effects of a non-selective endothelin receptor agonist, endothelin-1 (ET-1), and a selective ETB receptor agonist, sarafotoxin S6c. CHF was induced in dogs by rapid ventricular pacing and resulted in decreased left ventricular dp/dtmax, decreased cardiac output and increased pulmonary vascular resistance. Sarafotoxin S6c (0.3 nmol/kg) resulted in decreased left ventricular dp/dtma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our measurements of plasma ET-1 are consistent with values reported in human (1,6,13,20,24) and animal heart failure (3,22,25). Our larger dose of ET-1 (4.0 ng⅐ kg Ϫ1 ⅐min Ϫ1 ) is close to the upper limit of the pathophysiological range of ET-1 plasma levels reported earlier.…”
Section: Discussionsupporting
confidence: 80%
“…Our measurements of plasma ET-1 are consistent with values reported in human (1,6,13,20,24) and animal heart failure (3,22,25). Our larger dose of ET-1 (4.0 ng⅐ kg Ϫ1 ⅐min Ϫ1 ) is close to the upper limit of the pathophysiological range of ET-1 plasma levels reported earlier.…”
Section: Discussionsupporting
confidence: 80%
“…This is in accordance with a study in pigs with pacing‐induced heart failure, which showed that ET A receptor mRNA and ET A binding are increased (Ergul et al 2001). Similarly, data in dogs showed that, whereas pulmonary vasoconstriction in response to exogenous ET is predominantly mediated through the ET B receptor in normal dogs, there is an ET A ‐mediated component in dogs with pacing‐induced heart failure (Tadano et al 2004). Conversely, Docherty & MacLean (1998) investigated the effect of ET on isolated pulmonary arterioles in animals with MI using ET receptor agonists and antagonists, and found no contribution of the ET A receptor to pulmonary vasoconstriction in either normal rabbits or rabbits with MI.…”
Section: Discussionmentioning
confidence: 98%
“…Although improvements in peripheral vascular function have been observed following exercise regimens in human HF (18,22,43,53), the impact of exercise on the coronary vasculature has not been studied. Functional inadequacies of the peripheral and coronary vasculature, including altered reactions to mediators of vasoconstriction, such as ET-1, are well established in HF (8,21,32,33,46,49), implying exercise-dependent benefits extending to the coronary vasculature could directly impact LV function in HF. Much of the available literature demonstrates blunted coronary responsiveness to ET-1, as seen in a dog model of HF (8), and also following myocardial infarction in swine (35).…”
Section: Discussionmentioning
confidence: 99%
“…coronary circulation; vascular smooth muscle; potassium channels; heart failure CORONARY VASCULAR DYSFUNCTION is a hallmark feature of the progression to heart failure (HF). Altered responsiveness to mediators of vascular tone, such as endothelin-1 (ET-1), have been observed and may contribute to this phenomena (8,21,32,33,46,49). Impaired coronary vascular function can have profound effects on myocardial oxidative capacity and function and may play a significant role in the inability of the failing heart to respond to situations of increasing stress.…”
mentioning
confidence: 99%